Kimberlite and lamproite dykes from Holsteinsborg, West Greenland - Scott, Barbara H. (Meddelelser om Grønland. Geoscience, 1981)
Numerous kimberlite and lamproite dykes occur to the south and east of Holsteinsborg in Central West Greenland. This paper gives details of the petrography, mineral chemistry, age relations and geochemistry of the dykes. The kimberlites are composed of macrocysts of olivine, phlogopite, rare ilmenite and garnet in a matrix of olivine, phlogopite, diopside, perovskite, spinel, serpentine, carbonate and apatite. They can mostly be classified as clinopyroxene-phlogopite hypabyssal kimberlites. Mantle-derived inclusions are found in some of the dykes and include lherzolites, wehrlites, harzburgites and, most commonly, dunites. Both coarse and porphyroclastic inclusions occur. Garnet-granulites and eclogites, although rare, are present. The lamproites have variable mineral assemblages and textures but the main constituents are phenocrysts of pseudoleucite, olivine, phlogopite and clinopyroxene set in a groundmass of phlogopite, potassic richterite, diopside, pseudoleucite and potassium feldspar. The mineralogy of these dykes is a reflection of unusual ultrapotassic, magnesian whole-rock compositions.